MANAGERIAL PRINCIPLES IN PUBLIC EDUCATION AND THE PERFORMANCE OF THE TEACHER COORDINATOR - Landim, Vanessa [UNESP]; Borghi, Raquel Fontes [UNESP] (Unesp-faculdade Ciencias & Letras, 2020)
This article represents part of a master's degree research that investigates the acting of Teacher Coordinator in the face of large-scale evaluations implemented in Brazil from the 1990s. We will present some discussions about managerialism in Brazilian public education and indicate some possible influences on the performance of the Teacher Coordinator. For this, we dialog with Ball (2005a, 2005b), Ball e Youdell (2008), Fernandes (2004, 2008, 2009), Garcia, Adriao e Borghi (2009), Oliveira (2003), Paula (2005), Polato e Bertagna(2013). Based on the notes we can infer that the managerial principles began to exert influences on public education and on the performance of the Teacher Coordinator from the State reform that began in the 1990s in Brazil.
Keywords: Managerialism; Performativity; Public education; Teacher coordinator